Meningkatkan Hasil Belajar Pak Dengan Model Pbl Siswa Fase B Kelas 4 SD Negeri Kestalan Surakarta - Margareta Nataria (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education (PAK) for 4th-grade students at SDN Kestalan Surakarta using a Problem-Based Learning (PBL) model. The research was conducted in two cycles involving Phase B students. The results indicated a significant improvement in both cognitive learning outcomes and collaborative attitudes. In the first cycle, 33% of students achieved a